Tripodands with phenyl and thiophenyl rings and nitrogen bridgehead atoms - Baier, Martin; Gleiter, Rolf; Rominger, Frank (European journal of organic chemistry, 2006)
The flexible tripodands 7-9 and 15 with phenyl and thiophenyl rings as “legs” and nitrogen as bridgehead atoms have been synthesized by three-component condensation reactions of the corresponding amine with the aryl halide. The more rigid species 10-14 and 17 were built up from the podands 7-9 as well as from their iodine substitution products 33-35 by a sequence of ethynylation and C-C coupling reactions. Podand 16 was prepared from tris-iodide 36 by Sonogashira coupling with phenylacetylene. In the cases of 7, 12, 15-17, 22, 24, 35, 36, and 41 the structural parameters were determined by X-ray studies. With the exception of 7, 12, and 17, all structures show either close intermolecular contacts between heteroatoms (15, 22, 24, 35, and 36), C-H···N hydrogen bonding (41), or are closely packed as a result of π···π stacking (16). We were able to isolate silver triflate complexes of 9, 10, and 16, and in the case of 9 we obtained crystals suitable for X-ray diffraction studies. (© Wiley-VCH Verlag GmbH & Co. KGaA, 69451 Weinheim, Germany, 2006)
Gesehen am 29.09.2017